Analysis of the Application of Responsibility Accounting as a Cost Center Performance Assessment Tool at the Sintesa Peninsula Manado Hotel - Nellita Theresya Takalamingan; Stanly W. Alexander; Sherly Pinatik (Indonesian Journal of Entrepreneurship and Startups, 2024)
Responsibility accounting is a system that recognizes various centers of responsibility throughout an organization by assigning certain income and costs to the center that has the responsibility in question. This research aims to find out how responsibility accounting is implemented in assessing the performance of cost centers at the Sintesa Peninsula Manado Hotel. A qualitative strategy combined with techniques from descriptive analysis was used to perform this study. Interviews and documentation are the methods of data gathering employed in this study. The research's findings demonstrate that although this hotel has adopted responsibility accounting, it is not operating at its best. This is evident from the organizational structure, budget planning, classification of account codes, and accountability reporting. However, the classification of controllable costs and uncontrollable costs has not yet been carried out. The performance of the cost center at the Sintesa Peninsula Manado Hotel is considered quite good because it has worked in the planning process and controlled the costs incurred